PENGARUH PERPUTARAN PIUTANG DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABLITAS PADA SUB SEKTOR MAKANAN DAN MINUMAN - Muhammad Rivandi; Fitra Oliyan (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2022)
Profitability is an important element to assess the success of management in managing the company's fundamental financial performance. The purpose of this study is to see whether receivables turnover and sales growth have an effect on profitability. The population in this study is a Manufacturing Company in the Food and Beverage Sub-Sector. Company sample 11 companies selected by using purposive sampling method. Research method using panel regression. Based on the results of the study that accounts receivable turnover has a positive and significant effect on profitability and sales growth has no effect on profitability at the Food and Beverage Sub-Sector Manufacturing Company.